The behaviour, development, and health of the young child: implications for care. Issue 6380 (4th June 1983) - Bax, M; Hart, H; Jenkins, S
Abstract : Children with recurrent physical illnesses such as infections of the ears and chest are more likely than average to have developmental and behavioural disorders as well. Specialist skills are needed for the assessment and management of these disorders; the belief that "the child will grow out of it" is rarely correct. Any reorganisation of the child health services should take account of the need for children with developmental and behavioural disorders to be treated within the community by doctors and other health workers with the appropriate skills.